Future Arctic: how will increasing coastal erosion shape nearshore planktonic food webs? - Gabriel A. Juma; Cédric L. Meunier; Emily M. Herstoff; Anna M. Irrgang; Michael Fritz; Caroline Weber; Hugues Lantuit; Inga V. Kirstein; Maarten Boersma (Limnology and Oceanography Letters)
Abstract Arctic regimes. Currently, warming accelerates the erosion of permafrost coasts and the associated discharge of sediment, carbon, and nutrients into the Arctic Ocean. However, the impacts of coastal erosion on planktonic food webs remain understudied. We aimed to (1) understand how coastal erosion impacts nearshore carbon, nutrient, and light regimes; (2) investigate the effects on primary production and energy transfer; and (3) predict how increased erosion will impact the productivity of consumers, and the overall food web interactions. We found that sediment discharge increases turbidity (darkening). This darkening is expected to hamper phytoplankton productivity, while additional carbon input will provide bacteria with direct energy sources, and shift the balance between basal autotrophic and heterotrophic production. Since the heterotrophic pathway has a lower efficiency, its dominance might negatively affect mesozooplankton. Increased Arctic coastal erosion might therefore influence planktonic food webs by changing mechanisms of energy mobilization and transfer to higher trophic levels.